BENEFITS AND POSITIVE IMPACT ON THE HEALTH OF SECOND-YEAR STUDENTS USING TABLE TENNIS IN THE PRACTICE OF PHYSICAL EDUCATION AT THE NATIONAL TECHNICAL UNIVERSITY OF UKRAINE "IGOR SIKORSKY KYIV POLYTECHNIC INSTITUTE" - Irina Novikova (Scientific Journal of National Pedagogical Dragomanov University Series 15 Scientific and pedagogical problems of physical culture (physical culture and sports), 2026)
Table tennis is the most accessible game in the physical education curriculum for students. This is because table tennis, as a sport and active game, does not require significant material resources or space for training and competitions. Meanwhile, through the game, which is characterized by high physical activity, students develop such important qualities as speed, agility, coordination, attention, reaction time, eye, thinking, and other skills. Table tennis is an exciting, endlessly varied game, accessible to everyone, young and old. It is exciting and unpretentious. The ease and speed of movement, the swiftness of attacks and the dedication of defense, the unexpectedness of technical combinations make for a captivating spectacle. The variety of motor skills and actions, varying in coordination structure and intensity, contributes to the development of all physical qualities. During the game, participants receive a significant yet manageable physical load and, at the same time, an emotional boost. Table tennis fundamentals are part of the NTUU "Igor Sikorsky Kyiv Polytechnic Institute" curriculum. Students must master new elements of technique and tactics and become familiar with the basic rules of the game. Table tennis lessons are aimed at students' physical development, introducing them to discipline, daily routine, hygiene, and self-control. Table tennis is not only a fun game, but also a challenging and challenging exercise for willpower. The game accustoms a person to the physical and mental effort so necessary for work and everyday life. A student's table tennis training session involves technical, tactical, physical, psychological, and theoretical preparation. A training session should consist of three parts: preparatory (warm-up), main, and final, each with its own objectives. The goal of the preparatory part is to prepare all bodily functions. The main part of the session is aimed at mastering and refining technique and tactics, as well as developing moral and willpower. It is conducted with balls at the table. The final part of the session includes relaxation and breathing exercises, facilitating the body's gradual transition from intense exercise to rest. A warm-up is a set of specialized techniques aimed at preventing injury. Its purpose is to establish mutual coordination between the body's systems and individual organs. During a warm-up, the body's physiological functions-circulation, respiration, excretory functions, and psychophysical functions-are prepared for serious work. Attention is focused, precision of movement is improved, and optimal stimulation of the nervous system is achieved.